2003
DOI: 10.1007/s10123-003-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Enteric pathogens and soil: a short review

Abstract: It is known that soil is a recipient of solid wastes able to contain enteric pathogens in high concentrations. Although the role of soil as a reservoir of certain bacterial pathogens is not in question, recent findings show that soil may have a larger role in the transmission of enteric diseases than previously thought. Many of the diseases caused by agents from soil have been well characterized, although enteric diseases and their link to soil have not been so well studied. Gastrointestinal infections are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(111 citation statements)
references
References 26 publications
3
102
0
6
Order By: Relevance
“…Microcosm experiments are good model systems to study the survival of Salmonella in soil under defined laboratory or greenhouse conditions. Diverse factors such as temperature, pH and humidity, have been demonstrated to influence the fate of Salmonella (Santamaría and Toranzos, 2003; Jacobsen and Bech, 2012). Unfortunately, experiments analyzing these factors, even if performed in similar experimental settings, often lead to contrary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Microcosm experiments are good model systems to study the survival of Salmonella in soil under defined laboratory or greenhouse conditions. Diverse factors such as temperature, pH and humidity, have been demonstrated to influence the fate of Salmonella (Santamaría and Toranzos, 2003; Jacobsen and Bech, 2012). Unfortunately, experiments analyzing these factors, even if performed in similar experimental settings, often lead to contrary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that a range of human pathogens, including Salmonella , can survive extended periods of time in soils (Santamaria and Toranzos, 2003; Gerba and Smith, 2005; Bernstein et al, 2007a; Liu et al, 2010; Jacobsen and Bech, 2012). Two to four months survival periods for enteric bacteria in soil were reported in a review by Gerba et al (1975), and survival duration up to 29 weeks (Islam et al, 2004) was reported for Salmonella .…”
Section: Discussionmentioning
confidence: 99%
“…Further, use of water in postharvest processing has also played a role, for example, in trying to prevent importation of fruit flies [25]. It is well established that pathogens may be disseminated in the environment via the use of inadequately composted or raw animal manures or sewage [26, 27], via the faeces of wild animals [28], or via flies [29, 30]. Post-harvest processes, ranging from storage and rinsing to cutting, are also possible sources of contamination [31], and the use of inadequately decontaminated water in hydrocoolers, which are used to store and process large quantities of fresh produce, can lead to contamination of an entire lot [32].…”
Section: Discussionmentioning
confidence: 99%